Hydrocarbon Accounting Verification for Reasonable Assurance on EJGP Open Access Pipe System - Mildo Hasoloan Nainggolan; I Putu Suarsana; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2019)
The East Java Gas Pipeline (EJGP) pipeline network system is an open access for transporting almost ± 310 MMSCFD of Natural Gas from fields in East Java offshore to the onshore Power Plant consumers. The deviation between the calculated and mass balance of gas stock is called the Discrepancy in which BPHMIGAS set up a maximum value of ± 0.85%. The objective of the study is to develop a verification methodology to support hydrocarbon accounting in the EJGP Pipeline Network System. The methodology will be assisted by Flow Quantity Assurance software. After obtaining sufficient data, a new baseline can be taken empirically which can be used as a reference for the maximum allowable discrepancy in the EJGP Pipeline Network System. The data used in this simulation are taken from September - October 2013 such as pipes dimension of the entire network piping system, flowrate, pressure, temperature, and the composition of natural gas. The results of verification are compared with the calculations carried out by Pertamina Gas as operators. The calculation of Discrepancy from the Operators with different tools is around 0.12%, meaning that operator calculations are acceptable. The maximum allowable discrepancy ± 0.85%, can be reviewed to be reduced according to the history of the average system discrepancy in 2017-2018 (around 0.54%). The New Shipper from Sirasun Batur Field is still more economics by using the existing pipeline network even though it bears Discrepancy / Losses up to 1% compared to building new pipes to consumers. It is found that the discrepancy is getting smaller (reducing the error) if there is a gas balance, meaning that the end consumers will take the gas according to the agreed nomination.